Clinician experiences using standardised language assessments via telehealth. (2nd November 2021) - Sutherland, Rebecca; Hodge, Antoinette; Chan, Esther; Silove, Natalie
Abstract: Purpose : Telehealth is rapidly becoming an essential part of speech-language pathologists' core business, and yet the experiences and opinions of community-based therapists in using telehealth remain relatively unknown. This paper describes a recent study in which speech-language pathologists were provided with access to a formal language assessment within a telehealth platform and asked to provide feedback about their experiences. Method : Twenty-seven speech-language pathologists in paediatric practice were recruited via callouts on social media, community contacts and professional networks. The participants were provided access to a telehealth platform with a built-in formal language assessment and asked to use the assessment with their own caseload as clinically indicated and provide feedback after each assessment. Questionnaire data was collected via an online survey system and contained questions about each assessment including the most enjoyable and most difficult aspects of the assessment and their overall experience of the platform. Result : More than 100 assessments were completed during the 3-month trial, with clinicians reporting that on most occasions, video and audio quality was adequate or more than adequate, and that interactions with their child clients were effective. Qualitative data indicated that technical difficulties were a drawback to the assessments, but that ease of use of the assessment, the added functionality of using the assessment within the telehealth platform and factors including general benefits of telehealth, particularly that of being able to continue to provide services when face-to-face work was not possible were seen as positive elements. Conclusion : This study adds clinicians' voices to the research into telehealth, indicating that the assessment within the telehealth platform was generally easy to use, and provided an unexpected depth of insight and connection for clinicians and their clients. Future research may consider the voices of other stakeholders in telehealth interactions, including parents and child clients.